2016
DOI: 10.1038/srep31126
|View full text |Cite
|
Sign up to set email alerts
|

Control of cortex development by ULK4, a rare risk gene for mental disorders including schizophrenia

Abstract: Schizophrenia is a debilitating familial neuropsychiatric disorder which affects 1% of people worldwide. Although the heritability for schizophrenia approaches 80% only a small proportion of the overall genetic risk has been accounted for, and to date only a limited number of genetic loci have been definitively implicated. We have identified recently through genetic and in vitro functional studies, a novel serine/threonine kinase gene, unc-51-like kinase 4 (ULK4), as a rare risk factor for major mental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 67 publications
2
34
1
Order By: Relevance
“…However, the interaction between htra1 and apoptosis may be inferred from the down-regulation of gadd45b paralogues (qPCR validated) and serine/threonine-protein kinase ULK4 (microarray identified) by VEG diet. In mammals, GADD45B and ULK4 were related to the regulation of apoptosis through p38 MAPK signaling pathways [ 102 , 103 ], pathways in cross-talk with that of TGF-beta [ 104 ]. Piscine HTRA1 would require further investigation before drawing conclusions on its significance in salmon physiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction between htra1 and apoptosis may be inferred from the down-regulation of gadd45b paralogues (qPCR validated) and serine/threonine-protein kinase ULK4 (microarray identified) by VEG diet. In mammals, GADD45B and ULK4 were related to the regulation of apoptosis through p38 MAPK signaling pathways [ 102 , 103 ], pathways in cross-talk with that of TGF-beta [ 104 ]. Piscine HTRA1 would require further investigation before drawing conclusions on its significance in salmon physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CDC42 and actin skeleton remodelling have been associated with deficits in dendritic spine formation frequently reported in SCZ and BD (7678). Issues relating to neuronal network health, such as synaptic connectivity and neurite number have also been highlighted in both mental illness and PC dysfunction (53, 54, 7985).…”
Section: Neurodevelopmentmentioning
confidence: 99%
“…Interestingly, studies on the expression of ULK4 in Xenopus laevis suggested a possible role of this gene during forebrain neurogenesis and its involvement in migration processes [Dominguez et al, 2015]. Furthermore, CNVs of ULK4 are considered risk factors for neurodevelopmental and neuropsychiatric disorders, as such have been described in schizophrenia and autism patients [Lang et al, 2014[Lang et al, , 2016. Proper expression of ULK4 is essential for neuritogenesis and neuronal motility, and deficiency of Ulk4 compromises the development and integrity of the corpus callosum in mice [Lang et al, 2014].…”
mentioning
confidence: 99%